Study of deployment of Pre-Insertion resistor to disconnector for mitigating overvoltage on 525 kV current transformers - Filipe R. Gadotti; Sérgio H.L. Cabral; Felipe M. Schuartz (International Journal of Electrical Power & Energy Systems, 2024)
Because of the incidence of voltage pulse trains generated from intrinsic arcs existing during the operation of adjacent disconnectors, several failures in 550 kV class current transformers have been reported across the Brazilian integrated power grid. Based on previous correlated research, the authors present in this article computational results of their proposition in adopting the pre-insertion resistor-fitted disconnector type for addressing this issue, which is already indicated to be adopted in power substations with 800 kV or higher although for different reasons. With this aim, ATP modeling has been developed for analyzing a study case of a section of a bay of a 550 kV power substation. The obtained results indicate not only the drastic reduction in the overvoltage amplitude, in about 18 times less for the value of the Severity Factor, as well as in the significant reduction in both to one-third in the rate of the overvoltage rise and in the maximum amplitude of the current train pulses, which show this proposal to be technically promising. Yet, a study of the influence of the value of the pre-insertion resistor and the respectively adopted configuration is presented, based on what is commercially available in view of making this proposal to be economically viable.